Cerebrospinal nematodosis caused by Parelaphostrongylus species in an adult bull. (May 2020) - MacKay, Evelyn E.; Fratzke, Alycia P.; Gerhold, Richard W.; Porter, Brian F.; Washburn, Kevin E.
A 2-y-old Brahman bull was presented with progressive hindlimb ataxia and paraparesis that led to recumbency. Postmortem examination revealed scattered pinpoint, red-brown foci within the brainstem and gray matter of the spinal cord, and a larger lesion within the spinal cord at the level of T13. Histology of the section of T13 contained cross-sections of nematodes consistent with Parelaphostrongylus tenuis . Evidence of inflammation was present in other affected areas of the spinal cord and brain. DNA extraction and nested PCR were performed, which demonstrated 98% identity and 100% coverage to both P. tenuis and P. andersoni . Our case highlights the utility of DNA sequencing in parasite identification.